The impact of knowledge management on performance at work and the extent to which competitive advantage is achieved – General Directorate of Education, North Alsharqia Governorate, Sultanate of Oman as an Example – - Alyaarubi, Ali Saif Saud (Journal of Economic, Administrative and Legal Sciences, 2021)
This study seeks to determine the impact of knowledge management on performance at work and the extent of achieving competitive advantageIn the north-eastern region of the Sultanate of Oman, this requires: Determining what is the reality of knowledge management, how well the administrative staff realizes the concept of knowledge management, what is the role of knowledge management in improving the performance of internal operations and what are the proposals to develop institutional performance in the Directorate of Education in the North Eastern Province in the light of knowledge management processes?The researcher used the descriptive method and reached many results, most notably:• The degree of impact of the reality of knowledge management came in a medium degree, while the degree of influence of the administrative staff’s awareness of the concept of knowledge management is high. The impact of knowledge management operations currently practiced in the Directorate of Education in North Eastern Province in terms of diagnosis, setting goals for generation, storage, publishing, application) came to an intermediate degree, where knowledge and information are stored electronically for easy retrieval, with the need to pay more attention that the leadership work to reward employees according to their contributions in spreading knowledge.• There are statistically significant differences between the averages of the responses of the study individuals on knowledge management processes and their relationship to the distinction of institutional performance according to the variable of the academic qualification in the field of the level of excellence in institutional performance, where the level of significance was less than (0.05) and came in favor of the lowest category of diploma in the scientific qualification, This may be due to the lack of experience of this group to know the reality of the problem and its dimensions and deal with it less than other groups.The study recommends the following:1) Establishing a support team for the Quality Department representing the various departments in order to work on spreading the concept of knowledge management and organizing its operations.2) Work to include knowledge management within the strategic plans of the departments.3) Work to create a supportive culture to produce, share and invest knowledge.4) Adopting knowledge management as a standard for evaluating the performance of employees and departments.
Keywords: knowledge management; competitive advantage